A Heart and A Mind: Self-distancing Facilitates the Association Between Heart Rate Variability, and Wise Reasoning - Grossmann, Igor; Sahdra, Baljinder K.; Ciarrochi, Joseph (Frontiers in Behavioral Neuroscience, 2016)
Cardiac vagal tone (indexed via resting heart rate variability - HRV) has been previously associated with superior executive functioning. Is HRV related to wiser reasoning and less biased judgments? Here, we hypothesize that this will be the case when adopting a self-distanced (as opposed to a self-immersed) perspective, with self-distancing enabling individuals with higher HRV to overcome bias-promoting egocentric impulses and to reason wisely. However, higher HRV may not be associated with greater wisdom when adopting a self-immersed perspective. Participants were randomly assigned to reflect on societal issues from a self-distanced- or self-immersed perspective, with responses coded for reasoning quality. In a separate task, participants read about and evaluated a person performing morally ambiguous actions, with responses coded for dispositional vs. situational attributions. We simultaneously assessed resting cardiac recordings, obtaining 6 HRV indicators. As hypothesized, in the self-distanced condition, each HRV indicator was positively related to prevalence of wisdom-related reasoning (e.g., prevalence of recognition of limits of one’s knowledge, recognition that the world is in flux/change, consideration of others’ opinions and search for an integration of these opinions) and to balanced vs. biased attributions (recognition of situational and dispositional factors vs. focus on dispositional factors alone). In contrast, there was no relationship between these variables in the self-immersed condition. We discuss implications for research on psychophysiology, cognition, and wisdom.